Composite powder particle of open arc surfacing NbC phase reinforced high-boron alloy and application method
By preparing the composite powder of 10 to 12, the specific process steps and component distribution ratio is used to form an NBC phase with Austeen as the base to enhance the high boron alloy, which solves the resistance of high boron alloy in the abrasive wear of abrasives. The problem of lack of abrasion has realized the significant improvement of the micro -hardness and the optimization of wear performance.
Patent Information
- Application Number
- CN202411482472.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The existing high boron alloys are prone to cracking under wear conditions, have insufficient wear resistance, and the macro hardness of the austenite matrix is not high, making it difficult to effectively resist wear of the abrasive particles.
Composite powder with a particle size of 10 to 12 mesh is used and prepared through the process steps of sieve weighing, dry mixing, adding water glass to wet mixing, rotational bonding granulation, low-temperature sintering and powder screening to form austenite. It is a matrix NbC phase reinforced high boron alloy. The composite powder contains 21 to 23% B4C, 4 to 6% ferroniobium, 5 to 7% ferrotitanium and other components. Through the affinity of Ti, Nb and C, the granular MC phase is precipitated to form a high microscopic TiC and NbC phases of hardness.
The microscopic hardness increased to 1500 to 1900HV, the weight loss weight was reduced to 0.009g, which was far lower than the 0.03 to 0.05g of the average high boron alloy, which significantly improved the abrasion resistance.
Smart Images

Figure CN119346856A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant surfacing, and in particular relates to composite powder particles for open arc surfacing of NbC phase-reinforced high-boron alloy and an application method thereof. Background Art
[0002] Engineering machinery in the fields of metallurgy, mining, thermal power generation, etc., has severe abrasive wear conditions, the wear-resistant layer of the equipment is consumed quickly, and premature shutdowns cause considerable economic losses. How to improve the structure and morphology of the wear-resistant alloy to make it exhibit excellent wear resistance and increase its service life has become one of the goals that wear-resistant technicians have been striving to overcome.
[0003] Industrial wear-resistant alloys are mainly divided into two categories: high chromium and high boron alloys. The main wear-resistant phase of high chromium alloys is M 7 C 3 The main wear-resistant phase of high boron alloy is M 2 B, where M represents metal atoms such as Fe and Cr. The solubility of B in austenite and other matrices is less than 0.02% (mass percentage, the same below), while the solubility of C in austenite matrix can reach 2.11%. Therefore, compared with high chromium alloys, high boron alloys are more likely to precipitate primary M. 2 B shows higher abrasive wear performance. In addition, B resources are abundant in the earth's crust, and the cost of incoming materials is relatively low.
[0004] In addition, the high-boron alloy melt has high fluidity, and the boron atoms have a strong affinity with oxygen atoms, showing good self-deoxidation performance, which is more suitable for self-protected open arc cladding material components. 2 The BB bond of B in the
[002] crystal direction is relatively weak, which is also the reason for the 2 The preferred orientation of the B phase, i.e., the lath-shaped M 2 The length direction of the B phase is prone to cracking under the rolling action of the external load. 2 The surrounding of B phase is mostly (α-Fe+M 3 B) or (α-Fe+M 3 (C, B)) metamorphic eutectic, the structure is brittle and easy to crack under external load. 2 The surrounding of phase B is austenite with high plasticity, which can effectively alleviate the effect of external load on M. 2 The impact of phase B reduces cracking.
[0005] However, the austenite matrix is large in size and soft in nature, which makes it easy for abrasive particles to wedge into the alloy surface and reduce wear resistance. The overall macroscopic hardness of high-boron alloys with austenite as the matrix is not high, and the resistance to external abrasive particles is relatively small. This requires improving the austenite matrix structure and morphology to significantly increase its strength and obtain excellent wear resistance.
[0006] Therefore, developing a high-boron alloy with an austenite matrix and both high hardness and high wear resistance has become one of the technical challenges that technicians in the cladding industry need to solve. Summary of the invention
[0007] One of the purposes of the present invention is to provide a composite powder for open arc surfacing of NbC phase reinforced high boron alloy in view of the above-mentioned deficiencies of current surfacing materials.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] The composite powder particles are prepared by weighing the powder components contained therein, dry mixing, adding water glass to wet mixing, rotating and bonding the wet powder to granulate, sintering at low temperature, and screening the powder particles to form composite powder particles with a particle size of 10 to 12 meshes.
[0010] The weight percentages of the powder components contained in the composite powder particles are: 55-60% of metal chromium powder (Cr) with a chromium content of more than 99%; 21-23% of boron carbide (B) with a boron carbide content of more than 99%; 4 C); 4-6% of niobium-containing ferroniobium (FeNb60-A) with a niobium content of 58-62%; 5-7% of ferrotitanium (FeTi30-A) with a titanium content of 25-30%; 1.5-2.0% of ferrosilicon (FeSi45-A) with a silicon content of 40-47%; 1.5-2% of aluminum powder (Al) with an aluminum content of not less than 99%; the remainder is reduced iron powder (Fe) with an iron content of not less than 98%.
[0011] Furthermore, the powder components of metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon and reduced iron powder contained in the composite powder particles are passed through a 60-mesh sieve, and the aluminum powder is passed through a 200-mesh sieve and then weighed.
[0012] Furthermore, the water glass added to the dry mixed powder is of sodium silicate type, with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.3.
[0013] Furthermore, water glass was added to the dry mixed powder so as to be 20 to 30 ml of sodium silicate type water glass per 100 g of the dry mixed powder, and wet-mixed.
[0014] Furthermore, the rotation speed of the wet powder for bonding and granulation is 5 to 7 revolutions per second.
[0015] Furthermore, the composite powder particles are sintered at a low temperature of 280-320° C. and kept at this temperature for 2-4 hours before being taken out of the furnace.
[0016] The second object of the present invention is to provide an application method of the above-mentioned composite powder particles, namely: before welding, the composite powder particles are pre-placed on the weld, and an ER304 stainless steel solid welding wire with a diameter of Φ2.5mm (the chemical composition of this type of welding wire is equivalent to the H0Cr18Ni9 welding wire grade listed in the national standard GB / T17854-99) is used as a filling material. A DC power supply reverse connection method is used for self-shielded open arc surfacing welding. The arc generated between the solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld, and the composite powder particles are molten with the stainless steel solid welding wire droplets to form a surfacing pool, which is air-cooled and solidified into a NbC phase-reinforced high boron alloy with a filling rate (filling rate = composite powder particle melt weight / (composite powder particle melt weight + ER304 stainless steel solid welding wire melt weight)) of 0.45 to 0.50.
[0017] Furthermore, the surfacing welding current control value is 400-410A, and the welding machine trolley travel speed is 15.0-16.0m / h.
[0018] The composite powder of the present invention is used in combination with ER304 stainless steel solid welding wire to prepare a NbC phase-enhanced high-boron alloy by surfacing welding, and the alloy wear-resistant phase includes lath-shaped and block-shaped M 2 B phase (M includes two main alloying elements, Fe and Cr. Same below), granular NbC phase, cluster and strip M 23 (C,B) 6 phase, dot-like TiC phase and Fe 4 N phase (this phase is small in size, small in number, and mainly distributed in the austenite matrix). The composite powder can be used for surfacing wear-resistant alloys of parts that can withstand abrasive wear conditions under certain cyclic loads, such as surfacing the inner wall of a sandblasting pipe or the inner wall of a concrete delivery pipe.
[0019] Compared with the prior art, the present invention has the following innovative features and beneficial effects:
[0020] (1) The volume fraction of the main wear-resistant phase is high: the composite powder of the present invention adds 21-23% B 4 C, which provides a component content basis for the precipitation of high volume fraction boride. 2 B and newborn M 23 (C,B) 6 The volume fraction of the phase can reach 60-70%, which is much higher than that of the primary M phase in general high-boron alloys. 2 Phase B is at a level of 30-40%.
[0021] (2) The surrounding matrix of the boride is different: the main wear-resistant M 2 Phase B is distributed in block and lath shapes, and the main wear-resistant M 23 (C,B) 6The phase is distributed in clusters and strips, surrounded by a highly plastic austenite matrix, which allows it to relax some stress through plastic deformation of austenite under deformation and thermal shock. 3 B) or (α-Fe+M 3 (C, B)) and other brittle transformation eutectics precipitate, which enhances its toughness and significantly reduces the embrittlement tendency caused by high volume fraction of boride.
[0022] (3) Different TiC phase sizes: The size of TiC in the composite powder surfacing high-boron alloy of the present invention can reach 4 to 8 μm, which is significantly higher than the general level of 1 to 3 μm. These large-scale high microhardness TiC can act as strong wear-resistant particles to improve the wear resistance of the high-boron alloy.
[0023] (4) Different forms and quantities of NbC: The composite powder of the present invention only adds 4-6% ferroniobium to precipitate a certain amount of NbC phase. The core of this phase is TiC, that is, the NbC phase uses the TiC phase that precipitated first as the nucleus to make it dispersed. The migration and diffusion of carbon atoms is controlled by the above-mentioned carbon fixation method to prevent them from diffusing to the grain boundary and precipitating (α-Fe+M 3 B) or (α-Fe+M 3 (C, B)) brittle eutectic. At the same time, the austenite matrix is dispersed and strengthened due to the uniform precipitation of NbC phase, and the macroscopic hardness of the alloy is increased by 6-8HRC compared with the sample without niobium, which improves the wear resistance of the alloy.
[0024] (5) Excellent wear resistance: Although the prepared NbC phase reinforced high boron alloy is based on austenite, the microhardness of its surfacing alloy layer can reach 1500-1900 HV, and the weight loss due to wear is only about 0.009g, which is lower than the 0.03-0.05g of general high boron alloys, showing excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the microstructure diagram of the high boron alloy prepared in Example 1.
[0026] Figure 2 This is the phase composition diagram of the high boron alloy prepared in Example 1.
[0027] Figure 3 This is the microstructure diagram of the high boron alloy prepared in Comparative Example 1.
[0028] Figure 4 This is the phase composition diagram of the high boron alloy prepared in Comparative Example 1.
[0029] Figure 5 for Figure 1 The wear morphology of the high boron alloy prepared in Example 1 is shown.
[0030] Figure 6 for Figure 3 The wear morphology of the high boron alloy prepared in Comparative Example 1 is shown.
[0031] Figure 7 2. Microhardness distribution diagram of the vertical cross section of the high boron alloy layer prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the embodiments of the present invention are not limited thereto.
[0033] The composite powder particles of the present invention are prepared by the following steps: weighing the powder components contained therein, dry mixing, adding water glass to wet mixing, rotating and bonding the wet powder to granulate, sintering at low temperature, and screening the powder particles to prepare composite powder particles with a particle size of 10 to 12 meshes;
[0034] The weight percentages of the powder components contained in the composite powder particles are: 55-60% of metal chromium powder (Cr) with a chromium content of more than 99%; 21-23% of boron carbide (B) with a boron carbide content of more than 99%; 4 C); 4-6% of niobium-containing ferroniobium (FeNb60-A) with a niobium content of 58-62%; 5-7% of ferrotitanium (FeTi30-A) with a titanium content of 25-30%; 1.5-2.0% of ferrosilicon (FeSi45-A) with a silicon content of 40-47%; 1.5-2% of aluminum powder (Al) with an aluminum content of not less than 99%; the remainder is reduced iron powder (Fe) with an iron content of not less than 98%.
[0035] Before weighing the components, the powder components of metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon and reduced iron powder are sieved through a 60-mesh sieve, and the aluminum powder is sieved through a 200-mesh sieve before being weighed; then the powder components are weighed according to the composition ratio of the composite powder particles, and then all the powder components are placed in the same container and stirred thoroughly to mix evenly to form a dry mixed powder.
[0036] Following the previous step, add sodium silicate water glass with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.3 to the dry mixed powder by pouring 3 to 5 ml each time, until every 100 g of the above dry mixed powder finally contains 20 to 30 ml of water glass; during the addition, stir continuously to allow the water glass to evenly infiltrate the mixed powder, then rotate the container at a speed of 5 to 7 rpm to rotate and bond the wet powder into spherical wet powder particles, and let it stand for more than 5 minutes to set.
[0037] Next, the spherical wet composite powder particles are placed in a sintering furnace, heated to 280-320° C., kept at this temperature for 2-4 hours, and then taken out of the furnace.
[0038] Then, the sintered composite powder particles are first sieved through a 10-mesh sieve to remove large particles larger than 10 mesh; then sieved through a 12-mesh sieve to remove small particles smaller than 12 mesh, and finally composite powder particles with a particle size of 10 to 12 mesh are obtained.
[0039] On a Q235A steel plate with a length of 175mm, a width of 80mm, and a thickness of 20mm, composite powder particles are pre-placed on the weld bead before welding, and a solid ER304 stainless steel welding wire with a diameter of Φ2.5mm is used as the filling material. The arc generated between the solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld bead and melt the solid welding wire droplets to form a surfacing weld pool. The height and width of the pre-placed composite powder particle layer are optimized and regulated, and air-cooled solidification is performed to form a wear-resistant alloy with a powder filling rate of 0.45 to 0.50.
[0040] Before surfacing, set the polarity of the automatic welding machine ZD5-1000E to DC reverse connection, set the current value to 400-410A, the arc voltage to 30-35V, the welding wire extension to 30-35mm, the trolley travel speed to 15-16m / h, and keep the surfacing process parameters unchanged for each layer each time.
[0041] Self-shielded open arc welding is performed using the above-mentioned composite powder and ER304 stainless steel solid welding wire as surfacing materials, so that the composite powder melt and the ER304 stainless steel solid welding wire molten droplets are fused into a surfacing molten pool. After the molten pool is cooled and solidified, the first layer of weld is formed, which is air-cooled to room temperature to remove a small amount of slag on the weld surface; then the second layer is surfacing in the same way.
[0042] Based on this, the design principle of the composite powder and application method for open arc surfacing welding of NbC phase-reinforced high-boron alloy of the present invention can be summarized as follows: firstly prepare composite powder with a particle size of 10-12 mesh, use the composite powder and ER304 stainless steel solid welding wire as filling materials, and self-shielded open arc surfacing welding to form a high-boron alloy; use the ER304 stainless steel solid welding wire and the metal chromium powder of the composite powder to form a high-boron alloy with more than 22% Cr, significantly increase the volume fraction of primary boride and improve its phase toughness and microhardness; at the same time, optimize the type and content of the alloy component of the composite powder, use the affinity of Ti, Nb and C atoms to settle in the form of in-situ precipitation of granular MC phase, so as to reduce the hindering effect of high carbon atom clusters, and the primary M 2 Phase B and M 23 (C,B) 6 The growth of the phase is smooth, and the volume fraction of primary M is as high as 60-70%. 2 B and M 23 (C,B) 6 The main wear-resistant phase of the phase; the content of Ti, Nb and Si components is continuously optimized to regulate the number and distribution of carbon atoms, which not only increases the size of TiC, but also obtains an austenite matrix strengthened by NbC dispersion precipitation, significantly reducing the embrittlement tendency caused by high volume fraction of borides.
[0043] Example 1
[0044] Before weighing the components, the powder components such as metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: metal chromium powder 60%, boron carbide 22%, ferroniobium 6%, ferrosilicon 6%, ferrosilicon 1.5%, aluminum powder 1.5%, and reduced iron powder 3%.
[0045] Powder components such as metallic chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, aluminum powder and reduced iron powder are weighed according to the powder content contained in the above-mentioned composite powder particles, and then all the weighed powder components are put into the same container, stirred thoroughly to mix evenly, and form a dry mixed powder.
[0046] Next, 5 ml of sodium silicate water glass with a Baume degree of 30 and a modulus of 3.3 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 25 ml of water glass is finally added to every 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 6 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;
[0047] Next, the composite powder particles are placed in a sintering furnace and heated to 300°C, and then taken out of the furnace after being kept at this temperature for 3 hours. Then, the sintered composite powder particles are first sieved with a 10-mesh sieve to remove large particles larger than 10 mesh; and then sieved with a 12-mesh sieve to remove small particles smaller than 12 mesh, and finally composite powder particles with a particle size of 10 to 12 mesh are obtained.
[0048] Finally, on a Q235A steel plate with a length of 175 mm, a width of 80 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned screened composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated, and the alloy was air-cooled and solidified into a high-boron alloy with a powder filling rate of 0.48.
[0049] Before surfacing, the polarity of the automatic welding machine ZD5-1000E was set to DC reverse connection, and the surfacing process parameters were shown in Table 1.
[0050] The composite powder particles and ER304 stainless steel solid wire after sintering and sieving are used as filling materials for self-shielded open arc welding. The arc generated between the wire and the substrate is used to melt the composite powder particles and fuse them with the solid wire droplets to form a surfacing molten pool. When the molten pool is air-cooled and solidified to form the first layer of weld, the surface slag automatically falls off; then, the second layer is surfacing in the same way, and air-cooled and solidified to form a high-boron alloy with a powder filling rate of 47%. After welding, the weld surface is bright without defects such as cracks and pores.
[0051] Table 1 Composite powder and solid wire surfacing process parameters
[0052]
[0053] The wear resistance test was conducted using an MLS-225B wet sand rubber wheel wear tester. The test conditions were as follows: the rubber wheel had a diameter of 175 mm and a hardness of 60 Shore, the added weight was 2.5 kg, the rubber wheel speed was 240 rpm, and the mortar ratio was 1500 g of quartz sand of 40-60 mesh and 1000 g of tap water. The sample was pre-grinded for 1000 revolutions, rinsed, dried, and weighed for the initial weight M. 0 Then the formal test was carried out for 1000 revolutions, and then the sample was cleaned and dried, and the weight M 1 , the absolute weight loss of the sample due to wear ΔM=M 0 -M 1 .
[0054] The high-boron alloy described in Example 1 is used as a standard sample. The relative wear coefficient ε=absolute weight loss of the standard sample / absolute weight loss of the sample. The test results are shown in Table 2.
[0055] The microstructure, phase composition and wear morphology of the high boron alloy of Example 1 are shown in the attached drawings. Figure 1 , Attachment Figure 2 and attached Figure 5 The microhardness distribution of the vertical cross section of the high boron alloy layer is shown in the attached Figure 7 shown.
[0056] Example 2
[0057] Before weighing the components, the powder components such as metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: metal chromium powder 55%, boron carbide 21%, ferroniobium 5%, ferrosilicon 7%, ferrosilicon 2%, aluminum powder 1.5%, and reduced iron powder 8.5%.
[0058] Powder components such as metallic chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, aluminum powder and reduced iron powder are weighed according to the powder content contained in the above-mentioned composite powder particles, and then all the weighed powder components are put into the same container, stirred thoroughly to mix evenly, and form a dry mixed powder.
[0059] Next, 4 ml of sodium silicate water glass with a Baume degree of 32 and a modulus of 3.0 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 28 ml of water glass is finally added per 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 5 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is slightly vibrated, and the container is rotated until most of the composite powder particles have the same size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;
[0060] Next, the composite powder particles are placed in a sintering furnace and heated to 310°C, and then taken out of the furnace after being kept at this temperature for 3.5 hours. Then, the sintered composite powder particles are first sieved with a 10-mesh sieve to remove large particles larger than 10 mesh, and then sieved with a 12-mesh sieve to remove small particles smaller than 12 mesh, and finally composite powder particles with a particle size of 10 to 12 mesh are obtained.
[0061] Finally, on a Q235A steel plate with a length of 175 mm, a width of 80 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned screened composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated, and the alloy was air-cooled and solidified into a high-boron alloy with a powder filling rate of 0.49.
[0062] The remaining steps and wear resistance test contents are the same as those in Example 1.
[0063] Example 3
[0064] Before weighing the components, the powder components such as metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: metal chromium powder 58%, boron carbide 23%, ferroniobium 4%, ferrosilicon 7%, ferrosilicon 2%, aluminum powder 1.5%, and reduced iron powder 4.5%.
[0065] Powder components such as metallic chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, aluminum powder and reduced iron powder are weighed according to the powder content contained in the above-mentioned composite powder particles, and then all the weighed powder components are put into the same container, stirred thoroughly to mix evenly, and form a dry mixed powder.
[0066] Next, 4 ml of sodium silicate water glass with a Baume degree of 35 and a modulus of 3.2 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 24 ml of water glass is finally added per 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 5 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is gently vibrated, and the container is rotated until most of the composite powder particles have a uniform size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;
[0067] Next, the composite powder particles are placed in a sintering furnace and heated to 290°C, and then taken out of the furnace after being kept at this temperature for 4 hours. Then, the sintered composite powder particles are first sieved with a 10-mesh sieve to remove large particles larger than 10 mesh; and then sieved with a 12-mesh sieve to remove small particles smaller than 12 mesh, and finally composite powder particles with a particle size of 10 to 12 mesh are obtained.
[0068] Finally, on a Q235A steel plate with a length of 175 mm, a width of 80 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned screened composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated, and the alloy was air-cooled and solidified into a high-boron alloy with a powder filling rate of 0.46.
[0069] The remaining steps and wear resistance test contents are the same as those in Example 1.
[0070] Comparative Example 1
[0071] Before weighing the components, the powder components such as metal chromium powder, boron carbide, ferrotitanium, ferrosilicon, and reduced iron powder are first sieved through a 60-mesh sieve, and then the aluminum powder is sieved through a 200-mesh sieve. The contents (weight percentage) of the powder components contained in the composite powder particles are: metal chromium powder 60%, boron carbide 22%, ferrotitanium 6%, ferrosilicon 1.5%, aluminum powder 1.5%, and reduced iron powder 9%.
[0072] Powder components such as metallic chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon, aluminum powder and reduced iron powder are weighed according to the powder content contained in the above-mentioned composite powder particles, and then all the weighed powder components are put into the same container, stirred thoroughly to mix evenly, and form a dry mixed powder.
[0073] Next, 5 ml of sodium silicate water glass with a Baume degree of 30 and a modulus of 3.3 is added to the dry mixed powder each time, and stirring is continued during the addition to make the water glass evenly infiltrate the mixed powder, until 25 ml of water glass is finally added per 100 g of the dry mixed powder to form a wet powder; then the container is rotated at a speed of 6 revolutions per second to rotate the wet powder and bond it into composite powder particles; at the same time, large particles are crushed, the container is gently vibrated, and the container is rotated until most of the composite powder particles have the same size, and the composite powder particles are left to stand for 5 minutes to set, thereby obtaining approximately spherical composite powder particles;
[0074] Next, the composite powder particles are placed in a sintering furnace and heated to 300°C, and then taken out of the furnace after being kept at this temperature for 3 hours. Then, the sintered composite powder particles are first sieved with a 10-mesh sieve to remove large particles larger than 10 mesh; and then sieved with a 12-mesh sieve to remove small particles smaller than 12 mesh, and finally composite powder particles with a particle size of 10 to 12 mesh are obtained.
[0075] Finally, on a Q235A steel plate with a length of 175 mm, a width of 80 mm, and a thickness of 20 mm, an ER304 stainless steel solid welding wire with a diameter of Φ2.5 was used as an arc carrier; the above-mentioned screened composite powder particles were pre-placed in the weld, and the height and width of the pre-placed composite powder particle layer were optimized and regulated, and the alloy was air-cooled and solidified into a high-boron alloy with a powder filling rate of 0.48.
[0076] The surfacing welding process parameters, polarity setting and surfacing welding process of the automatic welding machine ZD5-1000E used in Comparative Example 1 are the same as those in Example 1. The wear resistance test content is the same as that in Example 1.
[0077] Comparative Example 1 The microstructure, phase composition and wear morphology of the surfacing high boron alloy are as follows: Figure 3 , Figure 4 and Figure 6 As shown in FIG. 1 , the high boron alloy of Comparative Example 1 was used as a comparative sample for the wear resistance test. The microhardness distribution of the vertical cross section of the high boron alloy layer of the sample is shown in FIG. Figure 7 shown.
[0078] Table 2 Abrasive wear resistance of high boron alloys prepared by surfacing welding in comparative examples and embodiments
[0079]
[0080] It can be seen from Table 2 that the relative wear coefficient ε of the composite powder surfacing high-boron alloy of the present invention is 1.89 to 1.91 times that of the surfacing alloy without the addition of niobium component composite powder, and the wear weight loss is lower than 0.03 to 0.05g of the ordinary high-boron alloy. Even the comparative sample is significantly higher than the ordinary high-boron. The selection of a large amount of metallic chromium powder and ER304 stainless steel solid welding wire significantly increases the chromium content of the alloy and significantly improves the wear resistance. After adding 4 to 6% of ferroniobium, not only the macroscopic hardness of the alloy is increased by 6 to 8HRC, but also the wear weight loss is reduced by about 90%, and the wear resistance is significantly improved, which shows that the high-boron alloy prepared by the composite powder of the present invention has excellent wear resistance.
[0081] By attaching Figure 1 and attached Figure 2 It can be seen that the high boron alloy structure prepared by the composite powder and ER304 stainless steel solid wire as welding materials is mainly composed of austenite (γ-Fe), ferrite (α-Fe(F)), M 2 Phase B, M 23 (C,B)6 phase, TiC phase, NbC phase and Fe 4 N and other phases. The intensity of the characteristic peak of austenite is large, indicating that its volume fraction is high; the intensity of the characteristic diffraction peak of ferrite is relatively small, indicating that its volume fraction is small. Figure 1 It can be seen that the alloy forms a structure with austenite as the main matrix. The macroscopic hardness of the alloy is 62.5-64.4HRC, which is high.
[0082] By the attached Figure 1 It can also be seen that the primary M in block, lath or mass form 2 Phase B and M 23 (C,B) 6 The volume fraction of the phase can reach 60-70%, which is much higher than the 30-40% level of the primary wear-resistant phase in general high-boron alloys. Figure 3 By contrast, the number of phases increases, the phase size decreases, and the overall volume fraction is not much different. It can be seen that the morphology of the main wear-resistant phase is significantly improved, which reduces the lamellar M 2 The accumulated stress of the directional growth of the B phase helps to reduce the probability of fracture. In addition, the white NbC phase grows with the black dot-like TiC phase that precipitated first as the nucleus, and this phase is dispersed in the austenite matrix to increase its strength and improve wear resistance.
[0083] The composite powder particles used in comparative example 1 differ from those in example 1 only in the ferroniobium component, and the other components and surfacing processes are exactly the same. Figure 3 and attached Figure 4 It can be seen that the microstructure of the high-boron alloy prepared in Comparative Example 1 is mainly composed of austenite (γ-Fe), ferrite (α-Fe(F)), M 2 Phase B, M 23 (C,B) 6 phase, TiC phase and Fe 4 N and other phases. The austenite characteristic peak has a high intensity, indicating that its volume fraction is large; the ferrite characteristic diffraction peak has a weak intensity, indicating that its quantity is rare. Figure 1 It can be seen that the alloy also forms a structure with austenite as the main matrix. The macroscopic hardness of the alloy is 56.4HRC, which is significantly lower than the high-boron alloy shown in the embodiment.
[0084] Compare with Figure 1 and attached Figure 3 It can be seen that the comparative example lacks the dispersion strengthening effect of the NbC phase, making this area easy for abrasive particles to wedge in. In addition, the lath M 2 The size of phase B is too large, and excessive internal growth stress is accumulated inside it, making it prone to local brittle cracking and peeling under the rolling action of external load.
[0085] Compare with Figure 5 and attached Figure 6The wear morphology of the two high-boron alloys shown in the figure shows that under the same wear test conditions, the high-boron alloy prepared by the composite powder surfacing welding of the present invention has no obvious scratches, the spalling pits are small and few, and are isolated. The wear of the entire surface is extremely uniform, and its wear mechanism is mainly the microscopic spalling of abrasive particles. Although the wear surface of the high-boron alloy shown in Comparative Example 1 has few and shallow scratches, the number of spalling pits is large and deep, and many of the spalling pits are continuously distributed, and many tiny cracks appear on the surface; these tiny cracks appear in the white block, corresponding to the primary M 2 B phase, indicating that its internal stress is too large; its wear mechanism is mainly the microscopic peeling of abrasive particles, and the wear weight loss is significantly higher than that of the high-boron alloy prepared by the composite powder particles of the present invention.
[0086] Compare with Figure 7 From the microhardness distribution of the vertical cross-section of the surfacing alloy layer of the comparative example and embodiment 1 shown, it can be seen that the microhardness of the high boron alloy layer of embodiment 1 is significantly higher than that of comparative example 1 by 200-500 HV, and the surfacing surface of embodiment 1 is basically above 1500 HV, and many areas are 1800-1900 HV, which has fully reached the level of cemented carbide.
[0087] The above results indicate that the high-boron alloy welded by the composite powder of the present invention has excellent wear resistance and can be used for welding wear-resistant alloy layers on parts in abrasive wear conditions, such as the inner wall of a sandblasting pipe or a concrete conveying pipe.
Claims
1. A composite powder for open arc cladding of NbC phase reinforced high boron alloy, wherein the powder components contained therein are subjected to sieve weighing, dry powder mixing, wet powder mixing by adding water glass, wet powder rotation bonding granulation, low temperature sintering, and powder particle screening to prepare composite powder particles with a particle size of 10 to 12 meshes; The weight percentages of the powder components contained in the composite powder particles are as follows: 55-60% of metal chromium powder containing more than 99% chromium; 21-23% of boron carbide containing more than 99% boron carbide; 4-6% of ferroniobium containing 58-62% niobium; 5-7% of ferrotitanium containing 25-30% titanium; 1.5-2.0% of ferrosilicon containing 40-47% silicon; 1.5-2% of aluminum powder containing not less than 99% aluminum; and the remainder is reduced iron powder containing not less than 98% iron.
2. The composite powder particles for open arc cladding of NbC phase reinforced high boron alloy according to claim 1, characterized in that: The powder components of metal chromium powder, boron carbide, ferroniobium, ferrotitanium, ferrosilicon and reduced iron powder contained in the composite powder particles are passed through a 60-mesh sieve, and the aluminum powder is passed through a 200-mesh sieve and then weighed.
3. The composite powder particles for open arc surfacing welding of NbC phase reinforced high boron alloy according to claim 1, characterized in that: The water glass added to the dry mixed powder is of sodium silicate type, with a Baume degree of 30 to 35 and a modulus of 3.0 to 3.
3.
4. The composite powder particles for open arc cladding of NbC phase reinforced high boron alloy according to claim 1, characterized in that: Water glass was added to the dry mixed powder in an amount of 20 to 30 ml of sodium silicate type water glass per 100 g of the dry mixed powder, and wet mixed.
5. The composite powder particles for open arc cladding of NbC phase reinforced high boron alloy according to claim 1, characterized in that: The rotation speed for bonding and granulating the wet powder is 5 to 7 revolutions per second.
6. The composite powder particles for open arc cladding of NbC phase reinforced high boron alloy according to claim 1, characterized in that: The composite powder particles are sintered at a low temperature of 280-320°C and kept warm for 2-4 hours before being taken out of the furnace.
7. A method for applying the composite powder as claimed in claim 1, characterized in that: Before welding, the composite powder particles are pre-placed on the weld bead, and the ER304 stainless steel solid welding wire with a diameter of Φ2.5mm is used as the filling material. The DC power supply reverse connection method is used for self-shielded open arc surfacing. The arc generated between the solid welding wire and the substrate is used to melt the composite powder particles pre-placed on the weld bead and the stainless steel solid welding wire droplets to form a surfacing pool, which is air-cooled and solidified into a NbC phase-reinforced high-boron alloy with a powder filling rate of 0.45-0.
50.
8. The method for applying the composite powder according to claim 7, characterized in that: The surfacing welding current control value is 400~410A, and the welding machine trolley travel speed is 15.0~16.0m / h.